TOXIC AND POTENTIALLY TOXIC ELEMENTS IN THE COAL OF THE SEAM С8 Н OF THE "BLAGODATNA" MINE OF PAVLOHRAD-PETROPAVLIVKA GEOLOGICAL AND INDUSTRIAL AREA - Nesterovskyi, V.; Ishkov, V.; Kozii, Ye. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Toxic elements in coal are one of the main sources of environmental pollution. Their content in coal is quite high, therefore the modern raising of ecological requirements needs taking into account the influence of coal-mining enterprises on state of environment. This causes the need of new scientifically grounded methods for forecasting the content of toxic and potentially toxic elements (TaPTE) in rock mass, as well as in mining waste and coal enrichment. In the article, the results of investigations of TaPTE in coal seam с8 н of "Blagodatna" mine field of Pavlohrad-Petropavlivka geological and industrial area of Donbas are considered, for the purpose of establishing regularities in their spatial distribution. The average content and lateral variations of TaPTE concentrations in coal seam were established, maps of the isoconcentrate of TaPTE and maps of the regional constituent of their contents in the area were constructed. The constructed maps are the factual basis for the long-term forecast of the concentrations of TaPTE in the rock mass extracted from mines. Linear regression equations are calculated, they characterize relationship between the concentrations of toxic and potentially toxic elements and the main technological parameters of the investigated layer. These equations can be used for short-term and mediumterm forecasting of TaPTE content in the extracted rock mass. In its turn, such forecasts should serve as the basis for technological solutions aimed at reducing their content in products and waste of coal enrichment. In addition, analysis of the result of statistical processing of geochemical information and geological and structural characteristics of the seam с8 нof mine field of "Blagodatna" mine indicates that the formation of the association of Co-Ni-V-Pb-Cr-Mn is associated with the enrichment of contact zones of the coal layer by these elements with thickness of 0,15-0,20m. The association of Hg and As is due to their genetic connection with the sulfide mineralization of fractured zones of tectonic nature.